Reduction of multiple pregnancy: Counselling and techniques. (January 2021) - Sebghati, Mercede; Khalil, Asma
Abstract: The incidence of multiple births has risen in the last few decades. This rise is mainly due to the widespread use of assisted reproduction techniques mainly as a result of increasing maternal age at conception. Twin and higher-order multiple pregnancies are associated with increased risk of perinatal, as well as maternal, mortality and morbidity compared to singleton pregnancies. There can also be psychosocial and socioeconomic implications for women and their families. In this chapter, we aim to discuss the risks associated with multiple pregnancies, the pros and cons of fetal reduction, the current techniques used in clinical practice, and how to approach counselling parents, enabling them to make informed decisions. Highlights: Discussion of causes of rise in the number of twin and higher-order multiple pregnancies in recent years. Discussion of maternal and perinatal risks associated with multiple pregnancies. Outline of managing multiple pregnancies including referral to Fetal Medicine unit and options available to prospective parents. Discussion of techniques employed for fetal reduction depending on chorionicity, level of expertise and availability of equipment. Outline of novel techniques of fetal reduction.